Structure systems - Engel, Heino ([Russia] : Hatje Cantz, 2009)
This work excel through sharp definition and articulation of contents, yet its true significance is to be seen in the fact that her, for the first time, the whole world of structures in building is brought into one comprehensive order under one single criterion, thus providing access to the multiplicity of all different structure system in full.
Basic systematics -- Form-active structure systems -- Vector-active structure systems -- Section-active -- Surface-active structure systems -- Height-active structure systems -- Hybrid structure systems -- Geometry structure form.
Includes bibliographical references.
Keywords: ARCHITECTURE -- STRUCTURAL ENGINEERING